Mesothelioma tumor cells modulate dendritic cell lipid content, phenotype and function - Gardner, J.; Mamotte, Cyril; Patel, P.; Yeoh, T.; Jackaman, Connie; Nelson, Delia (Public Library of Science, 2015)
Dendritic cells (DCs) play an important role in the generation of anti-cancer immune responses, however there is evidence that DCs in cancer patients are dysfunctional. Lipid accumulation driven by tumor-derived factors has recently been shown to contribute to DC dysfunction in several human cancers, but has not yet been examined in mesothelioma. This study investigated if mesothelioma tumor cells and/or their secreted factors promote increases in DC lipid content and modulate DC function. Human monocyte-derived DCs (MoDCs) were exposed to human mesothelioma tumor cells and tumor-derived factors in the presence or absence of lipoproteins. The data showed that immature MoDCs exposed to mesothelioma cells or factors contained increased lipid levels relative to control DCs. Lipid accumulation was associated with reduced antigen processing ability (measured using a DQ OVA assay), upregulation of the co-stimulatory molecule, CD86, and production of the tolerogenic cytokine, IL-10. Increases in DC lipid content were further enhanced by co-exposure to mesothelioma-derived factors and triglyceride-rich lipoproteins, but not low-density lipoproteins. In vivo studies using a murine mesothelioma model showed that the lipid content of tumor-infiltrating CD4+CD8a- DCs, CD4-CD8a- DCs and plasmacytoid DCs increased with tumor progression. Moreover, increasing tumor burden was associated with reduced proliferation of tumor-antigen-specific CD8+ T cells in tumor-draining lymph nodes. This study shows that mesothelioma promotes DC lipid acquisition, which is associated with altered activation status and reduced capacity to process and present antigens, which may impair the ability of DCs to generate effective anti mesothelioma T cell responses.